Reliability Testing Platform of Rubber Elastomeric Component for Rail Vehicle - LINDa-wen; WANGJin; PENGLi-qun; LIXin; ZHANGZhi-qiang (机车电传动)
For solving the key technic problem of rubber elastomeric component combinational loading test for rail vehicle,a modular design concept was presented.A 12-channel combinational loading test platform was constructed,design principle and structure of which were introduced,and typical products were tested.Design parameters of the platform were proved to satisfy the test requirement well,which provided researching platform for rail vehicle elastomeric component safety and reliability study in China.